Effect of tension stiffening on the behaviour of reinforced concrete circular columns under torsion. (1st June 2015) - Mondal, Tarutal Ghosh; Prakash, S. Suriya
Highlights: Tension stiffening effect on behaviour of RC circular columns under torsion is studied. Three different tension stiffening models are considered for evaluation. Exponential tension stiffening model yielded the best prediction. Linear tension stiffening model failed to predict the behaviour in the post peak region. Failure progression was captured well by the circular tension stiffening softened truss model. Abstract: Combination of torsion and axial compressive loading frequently occurs in bridge columns during earthquake vibrations. However, very few investigations in the past have explored the behaviour of Reinforced Concrete (RC) members under such load combinations. Softened Truss Model (STM) can be used to predict the torsional response of RC members such as beams and columns. In the present study, STM is used to predict the behaviour of RC circular columns under combined action of torsion and axial compression and the analytical prediction has been compared with experimental observation. It has been found that the overall torque–twist curve and in particular the post-peak behaviour of the tested columns is not accurately predicted by the original STM. The present study focuses on development of an improved analytical model for RC circular columns under torsional load conditions. The tensile strength of concrete being very small, its contribution to torsional strength of RC members was considered insignificant and was neglected in the original STM. The present investigation revealed that neglecting tension stiffening is the main reason behind the less accurate predictions of STM in the past compared to test data. The original STM has been extended in this study to include the effect of tension stiffening (TS) to get an improved prediction. Three different tension stiffening models have been considered for this purpose. The efficiency of each model in predicting the overall torsional response of RC columns under combined torsion and axial compression has been validated by comparing the analytical predictions of TS-STM with experimentally observed values. It is observed that exponential tension stiffening model can best represent the torsional behaviour of circular RC columns.